Selective Laser Sintering as Manufacturing Process for the Realization of Complex Nuclear Fusion and High Heat Flux Components. (17th November 2017) - Neuberger, Heiko; Rey, Joerg; Hees, Manuel; Materna-Morris, Edeltraud; Bolich, Daniel; Aktaa, Jarir; Meier, Andreas; Fischer, Stephen; Schorle, Cornelia; Fuhrmann, Uwe; Heger, Rainer; Dlouhý, Ivo; et al.
Abstract: The development of fabrication technologies for ITER and DEMO Blanket concepts is an activity followed by the KIT since a long time. A variety of fabrication technologies has been developed and qualified in strong collaboration with industry. Besides the standard technologies, an activity has been launched to explore the capabilities of generative fabrication procedures such as Laser Beam Melting (LBM) and Selective Laser Sintering (SLS). To manufacture demonstrator parts for Blankets by LBM /SLS, EUROFER (a Reduced Activation Ferritic Martensitic/RAFM steel applied e.g. in ITER) has been produced as powder metallurgical product. With this material, test parts have been realized. The test program started with solid parts and simple geometries used for extraction of specimen for material qualification purpose. Later, more complex parts were fabricated to investigate the feasibility of hollow and double walled structures and components with internal channel structures. Finally, blanket relevant part segments (e.g. for the Stiffening Plates) with meandering cooling channel structures and Flow Channel Insert segment demonstration parts for the EU Helium Cooled Pebble Bed and the Dual Coolant Lithium Lead Breeder Blanket concepts for DEMO have been fabricated. First preliminary qualification activities have been concluded using test procedures applied e.g. for the qualification of welding seams such as Tensile – and Charpy tests, macro- and micro structure investigation or hardness measurement. The findings have been compared to standard material properties of EUROFER in order to quantify the fabrication results. Material properties of 80% and more, compared to standard rolled EUROFER with comparable heat treatment history could be demonstrated in case of Tensile- and Yield- strength, total strain after fracture as well as energy consumption in Charpy tests. Also the joining of generatively fabricated sub-components together with conventionally fabricated EUROFER parts by Electron Beam welding has been investigated in order to test the option of the fabrication of hybrid components. These hybrid components are intended to combine parts with straight channels fabricated by Electrical Discharge Machining together with generative fabricated parts with complex structures of cooling channels (e.g. nested U-shaped flow paths) which cannot be realized using standard machining technologies. This technical note reports the first promising qualification results of generatively fabricated EUROFER parts. Also the weldability of generative fabricated parts and conventionally fabricated EUROFER has been demonstrated. Preliminary qualification results of the welding are shown, and possibilities for experimental qualifications are discussed.